Analgesic and anti-inflammatory activities of the water extract from terminalia chebula rezt - Sireeratawong,S. (African Ethnomedicines Network, 2015)
© 2014, African Ethnomedicines Network. All right reserved. Background: In ayurvedic and Thai traditional medicine, the fruit of T. chebula is useful in arthritic disorders, inflammation, tumor, pains, chronic and recurrent fever. The study investigated the analgesic and anti-inflammatory activities in animal models. Materials and methods: The water extract of T. chebula fruit was prepared and pain induced in mice by 0.1% formalin, before testing for the analgesic activity of the extract. The anti-inflammatory study was conducted in rats using four experimental models; ethyl phenylpropiolate or arachidonic acid-induced ear edema, carrageenan-induced paw edema and cotton pellet-induced granuloma formation. Results: The T. chebula extract decreased licking times in mice injected with 0.1% formalin in both the early and late phases. Moreover, the extract inhibited rat ear edema induced by ethyl phenylpropiolate as well as in carrageenan-induced paw edema. In contrast, the extract did not have any inhibitory effect on arachidonic acid-induced ear edema in rats. The T. chebula extract did not reduce granuloma weight, body weight gain and thymus dry weight in cotton pellet-induced granuloma formation. Conclusion: These results likely suggest that T. chebula water extract possess both analgesic and anti-inflammatory activities. The main mechanisms of action of T. chebula water extract may be due to the inhibitory effect on the synthesis and/or release of pain or inflammatory mediators.